A brief overview of biomechatronics and its applications - Rashid, Nur Izatulnisha; Kassim, Jamaliah; Abdul Muthalif, Asan Gani (IIUM Press, 2011)
"The Six Million Dollar Man" is a very popular TV series in which the scientists restore a crippled test pilot, who lost legs, one arm and an eye. In this series, the scientists are shown to have the relevant technology, thus they rebuild the injured pilot and give him superhuman qualities. Although the technology used in this TV series is total science fiction, however, modern robotics is inching ever closer to fulfill this vision [1]. Modernization of the era, has allowed the scientists to develop such technology; the so called “fiction” in the series by adopting biomechatronics approach in its design. As biomechatronics seem to give much credit to humanity, thus recently, many researchers put much effort into this field and come out with various new, useful and natural biomechatronics devices. For instance, in the year 2006, Dr. Todd Kuiken at the Rehabilitation Institute of Chicago developed a prosthetic arm for Claudia Mitchell, a former Marine and amputee, who lost her arm in a battle [2]. In this chapter, some discussion on Biomechatronics will be point out. The rest of the chapter is organized as follows; section 1.2 gives an overview of Biomechatronics and the components embedded in the system. This is followed by the applications and prospects of Biomechatronics in section 1.3. The continuing section is on its advantages and disadvantages, and finally the conclusion.